Clinical significance and biological role of cancer‐derived Type I collagen in lung and esophageal cancers. Issue 2 (3rd January 2019) - Fang, Shuo; Dai, Yongdong; Mei, Yan; Yang, Mingming; Hu, Liang; Yang, Hong; Guan, Xininyuan; Li, Jiangchao
Abstract : Background: Extracellular matrix (ECM) is remodeled during carcinogenesis. An abundant constituent of ECM is collagen. Type I collagen is secreted by fibroblasts, is important for tumor growth and epithelial‐mesenchymal transition, and may also be secreted by cancer cells. However, the role and function of cancer‐derived Type I collagen in the tumor microenvironment remains unclear. Methods: We used immunohistochemistry and Western blot to detect Type I collagen expression in non‐small cell lung cancer (NSCLC) and esophageal squamous cell carcinoma (ESCC) cell lines, respectively. We assessed the migration and adhesion capability of these cells in vivo by inhibiting Type I collagen in tumors. Relevant data were extracted from a large cohort study of The Cancer Genome Atlas to analyze messenger RNA levels. Protein expression of Type I collagen was further determined in tumor tissues of patients using tissue microarray. Results: Cancer cell lines secreted Type I collagen. The molecular weight of cancer‐derived Type I collagen was different from that secreted by cancer‐associated fibroblasts and normal fibroblasts. Expression levels of COL1A1 and COL1A2 (subtypes of Type I collagen) messenger RNA in NSCLC and ESCC tumors were higher than in normal tissues, but were not associated with tumor node metastasis stages. Low expression of Type I collagen was significantly associated with poor overall survival and cancer cell differentiation. Conclusion: NSCLC and ESCC cells could produce Type I collagen endogenously, revealing the potential functions of Type I collagen in cancer development. Cancer‐derived Type I collagen was associated with overall survival and cancer cell differentiation.